Kemampuan Berbicara Anak Usia 5-6 Tahun di TK X Kamal - Alfatihaturrohmah Alfatihaturrohmah; Dewi Mayangsari; Muhammad Busyro Karim (PG-PAUD Trunojoyo, 2018)
This research has a purpose to describe of the ability to speak children aged 5-6 years in school.This research uses qualitative approach descriptive method. Data analysis is done through three stages: data reduction, display data, and conclusions: drawing / verifying. Subjects in this study 1 girls aged 5-6 years. The results of this study indicate that 1) the characteristics of the ability to speak children aged 5-6 years in X Kindergarten of Kamal ie children are able to participate in the conversation without monopolizing, but the child has not been able to use words related to the sequence of events, not able to use the word tomorrow and yesterday, the child is only able to say 6 to 7 syllables, the child has not been able to answer the question regularly group activities for 10-15 minutes, the child is only able to use sentences 3 to 4 words. The child also has not been able to answer the question "when", the child is more often silent when others ask because the child has problems speaking. 2) There are obstacles that arise in the ability to speak of children is the phonological process constraints.